2014
DOI: 10.1126/science.1252114
|View full text |Cite
|
Sign up to set email alerts
|

FoxP influences the speed and accuracy of a perceptual decision in Drosophila

Abstract: Decisions take time if information gradually accumulates to a response threshold, but the neural mechanisms of integration and thresholding are unknown. We characterized a decision process in Drosophila that bears the behavioral signature of evidence accumulation. As stimulus contrast in trained odor discriminations decreased, reaction times increased and perceptual accuracy declined, in quantitative agreement with a drift-diffusion model. FoxP mutants took longer than wild-type flies to form decisions of simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
154
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(170 citation statements)
references
References 34 publications
13
154
3
Order By: Relevance
“…Using green fluorescent protein to report FoxP promotor activity, Lawton et al (2014) saw expression in the so called central complex, that has been hypothesized (Strausfeld & Hirth, 2013) to be functionally analogous to the vertebrate basal ganglia. In contrast, using a slightly different promoter sequence, DasGupta et al (2014) did not find FoxP expression in the central complex at all but in the core region of the mushroom bodies instead, a multimodal integration site in the fly brain that is important for learning and memory. These differences might also account for the fact that in one study motor behavior (walking) was reported to be normal (DasGupta et al, 2014) whereas in other studies (Lawton et al, 2014) motor behavior was impaired.…”
Section: N Common Themesmentioning
confidence: 81%
See 3 more Smart Citations
“…Using green fluorescent protein to report FoxP promotor activity, Lawton et al (2014) saw expression in the so called central complex, that has been hypothesized (Strausfeld & Hirth, 2013) to be functionally analogous to the vertebrate basal ganglia. In contrast, using a slightly different promoter sequence, DasGupta et al (2014) did not find FoxP expression in the central complex at all but in the core region of the mushroom bodies instead, a multimodal integration site in the fly brain that is important for learning and memory. These differences might also account for the fact that in one study motor behavior (walking) was reported to be normal (DasGupta et al, 2014) whereas in other studies (Lawton et al, 2014) motor behavior was impaired.…”
Section: N Common Themesmentioning
confidence: 81%
“…In contrast, using a slightly different promoter sequence, DasGupta et al (2014) did not find FoxP expression in the central complex at all but in the core region of the mushroom bodies instead, a multimodal integration site in the fly brain that is important for learning and memory. These differences might also account for the fact that in one study motor behavior (walking) was reported to be normal (DasGupta et al, 2014) whereas in other studies (Lawton et al, 2014) motor behavior was impaired. Needless to say, the devil with experimental conditions lies in the details and follow up studies using more approaches to determine where FoxP mRNA and protein is expressed in the nervous system of developing and adult flies as well as honey bees will refine the currently still confusingly complex results of the compare and contrast approach.…”
Section: N Common Themesmentioning
confidence: 81%
See 2 more Smart Citations
“…This approach has been applied successfully to study the behavioral evaluation of courtship songs (Clemens and Hennig 2013;Clemens et al 2015a). When extended with a behavioral threshold, such models resemble so-called "drift diffusion models", which integrate sensory information -in this case the output of the LN model -to a decision boundary, the crossing of which corresponds to decision making (Brunton et al 2013;DasGupta et al 2014;Clemens et al 2014).…”
Section: Extensions Of the Standard Linear-nonlinear Modelmentioning
confidence: 99%